Biodiversity of Angola 2019
DOI: 10.1007/978-3-030-03083-4_14
|View full text |Cite
|
Sign up to set email alerts
|

The Avifauna of Angola: Richness, Endemism and Rarity

Abstract: Angola has a rich history of ornithological exploration going back to the early 1800s. From the early-1970s to 2002, however, the civil war prevented access to many areas, and very little work on birds was done. From about the early 2000s information on birds in Angola has been gathered at an increasing rate, with new species being added to the list and a steady rise in publications on biogeography and biology of birds. With about 940 species, Angola has an impressive array of bird species, including c. 29 end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…What is equally important in biogeographic analysis is the detection of patterns of endemism and diversity at dispersed scales -such as the Angolan Escarpment Zone -described by Hall (1960a) and subsequently recognised by many workers as of great biodiversity and evolutionary importance (Huntley 1973(Huntley , 1974a(Huntley , 2017Hawkins 1993;Mills 2010;Clark et al 2011). Indeed, each taxon-based account in this volume, on plants (Goyder and Gonçalves 2019), odonata (Kipping et al 2019), lepidoptera (Mendes et al 2019), fishes (Skelton 2019), birds (Dean et al 2019), amphibians (Baptista et al 2019), reptiles (Branch et al 2019) and mammals (Beja et al 2019) draws attention to the importance of the Angolan Escarpment as a centre of endemism and speciation. Hall (1960a) explained her recognition of the importance of the Angolan Escarpment as the major speciation hotspot for birds in Angola by it: (i) creating a barrier between arid-adapted species of the coastal plains and of the miombo woodlands of the plateau, (ii) creating a steep ecological gradient, and (iii) functioning as a refuge for moist forest specialists that were isolated here during the dry periods of the glacial cycles.…”
Section: The Biological Importance Of the Angolan Escarpmentmentioning
confidence: 90%
See 1 more Smart Citation
“…What is equally important in biogeographic analysis is the detection of patterns of endemism and diversity at dispersed scales -such as the Angolan Escarpment Zone -described by Hall (1960a) and subsequently recognised by many workers as of great biodiversity and evolutionary importance (Huntley 1973(Huntley , 1974a(Huntley , 2017Hawkins 1993;Mills 2010;Clark et al 2011). Indeed, each taxon-based account in this volume, on plants (Goyder and Gonçalves 2019), odonata (Kipping et al 2019), lepidoptera (Mendes et al 2019), fishes (Skelton 2019), birds (Dean et al 2019), amphibians (Baptista et al 2019), reptiles (Branch et al 2019) and mammals (Beja et al 2019) draws attention to the importance of the Angolan Escarpment as a centre of endemism and speciation. Hall (1960a) explained her recognition of the importance of the Angolan Escarpment as the major speciation hotspot for birds in Angola by it: (i) creating a barrier between arid-adapted species of the coastal plains and of the miombo woodlands of the plateau, (ii) creating a steep ecological gradient, and (iii) functioning as a refuge for moist forest specialists that were isolated here during the dry periods of the glacial cycles.…”
Section: The Biological Importance Of the Angolan Escarpmentmentioning
confidence: 90%
“…Hall (1960a) explained her recognition of the importance of the Angolan Escarpment as the major speciation hotspot for birds in Angola by it: (i) creating a barrier between arid-adapted species of the coastal plains and of the miombo woodlands of the plateau, (ii) creating a steep ecological gradient, and (iii) functioning as a refuge for moist forest specialists that were isolated here during the dry periods of the glacial cycles. Dean et al (2019) note that 75% of Angola's endemic birds are found in this zone. The Angolan Escarpment and the remote, isolated and fragmentary remnants of Afro-montane forests of the Angolan Highlands offer ideal testing grounds for biogeographic models, as recently explored by Vaz da Silva (2015).…”
Section: The Biological Importance Of the Angolan Escarpmentmentioning
confidence: 96%
“…Estes and Estes (1974) undertook detailed behavioural studies of Giant Sable in Luando in 1970/71. Huntley undertook general ecological surveys in the protected areas and across most of Angola (Huntley 1973(Huntley , 1974d(Huntley , 2017, while Dean (2000) studied the avifauna of Angola in the field and in the key collections of museums of Angola, Europe and the USA. But it was not until the present century that more detailed studies were initiated in the protected areas of Angola, such as the long-term studies of Giant Sable in Cangandala and Luando by Vaz Pinto (2018) and of sea turtles on the Angolan coast (Kitabanga Project 2017).…”
Section: Drivers Of Species Lossmentioning
confidence: 99%
“…But it was not until the present century that more detailed studies were initiated in the protected areas of Angola, such as the long-term studies of Giant Sable in Cangandala and Luando by Vaz Pinto (2018) and of sea turtles on the Angolan coast (Kitabanga Project 2017). Nevertheless, there have recently been important surveys of the remnant populations of large mammals in the protected areas of Angola (Beja et al 2019), and on the threatened and endemic avifauna of the escarpment (Dean et al 2019).…”
Section: Drivers Of Species Lossmentioning
confidence: 99%
“…With fifteen ecoregions (Olson et al 2001;Burgess et al 2004;, Angola is one of the most biodiverse countries of the world, so biological collections will or should reflect that diversity. The number of endemic species is recognised to be high in several groups, for example in birds (Mills and Melo 2013;Dean et al 2019) and plants (Figueiredo et al 2009a, b;Goyder and Gonçalves 2019). However, despite this richness, the Angolan Escarpment could not be recognised as one of the biodiversity hotspots of the world due to the lack of information on its species diversity (Myers et al 2000).…”
Section: Introductionmentioning
confidence: 99%